E-Cigarette Use and Perceptions Among Veterans Receiving Outpatient Treatment in Veterans Affairs Substance Use and Mental Health Clinics. Issue 1 (30th January 2021) - Dixit, Devika; Herbst, Ellen; Das, Smita
ABSTRACT: Introduction: Individuals with substance use disorders and/or mental health (MH) conditions have higher rates of cigarette smoking than the general population. Electronic nicotine delivery systems (ENDS) while gaining popularity pose health risks. Herein we investigate risk perceptions and attitudes toward e-cigarettes in military Veterans with MH conditions. Materials and Methods: Participants included U.S. Veterans receiving services from Veterans Administration MH/substance use disorder clinics in the San Francisco Bay Area (N = 98; 95% male, 44% White, 34% Black/African American), who completed a survey on smoking and health. Results compare attitudes and perceptions regarding e-cigarette use between ever and never e-cigarette users. The study was reviewed by the Institutional Review Board at both the Veterans Administration and University. Results: Most respondents reported being current/past cigarette smokers (91%) and over a third reported having ever used an e-cigarette (38%). Most believed that e-cigarettes are not safe, are potentially dangerous, are potentially addictive if they use every day and are tempting and appealing to youth. Fifty-one percent of ever-users agreed with a statement that e-cigarettes can help people quit smoking regular cigarettes completely, and there was a significant difference in this belief when comparing them with never-users (23% agreed); χ 2 = 9.259, P = 0.010. Conclusions: Proportion of e-cigarette use in this Veteran sample is greater than the general population. We observed high risk perception about e-cigarettes among all respondents and differences in perceived helpfulness of e-cigarettes for quitting in ever-users versus never-users in this sample. More consistent assessment of tobacco use among Veterans, with inclusion of ENDS use, would help inform prevention and treatment priorities, especially as information on health impacts of ENDS surfaces.